Evaluasi Dan Perancangan Rekomendasi Tata Kelola Teknologi Informasi Mengguunakan Cobit 2019 - Sangka, Yuliana; Tonapa, Jennis; Worabai, Engelberth (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2026)
The development of Information Technology (IT) currently encourages companies or organizations to optimize and improve operational efficiency and service quality. Cafe XYZ is one of the businesses engaged in the culinary field that currently utilizes IT in managing sales data and business operations. However, in its implementation, it still does not use appropriate standards, causing operational processes to be slow, such as the cashier section often experiences errors in recording transactions and often experiences data loss. This study aims to provide recommendations for improvements based on the COBIT 2019 standard. The method used in this study is the COBIT 2019 framework by measuring the level of IT process capabilities expected with the current one, which is measured using the COBIT 2019 Toolkit and questionnaires. The results of the study indicate that there is a gap between the current level of IT process capabilities and those expected in the APO12 process objective and DSS01, DSS03 and DSS05. Therefore, IT governance improvements are needed through strengthening security mechanisms and incident handling. With these recommendations, it is hoped that IT management at Cafe XYZ can be effectively improved